Convergence across countries and regions: Theory and empirics - Angel de la Fuente (EIB Papers, 2000)
In the last decade or so, growth has come to occupy an increasingly important place among the interests of macroeconomists, displacing to some extent their previous preoccupation with the business cycle. This change is largely due to two factors. The first one is the realisation that, in terms of medium and long-term welfare, the trend is more important than the cycle - provided the volatility of income remains as low as it has been during the last few decades (Lucas, 1987). The second factor is the increasing dissatisfaction with the traditional neo-classical models that summarised the pre-existing consensus on the determinants of growth - essentially because of their perceived inability to account for such key features of the data as the observed increase in international inequality or the absence of capital flows toward less developed countries.
Keywords: 330; Entwicklungskonvergenz; Wachstumstheorie; Theorie